THE FIRST WORLD WAR AND THE APPEARANCE OF THE THEME OF THE “LOST GENERATION” IN LITERATURE - Dilnoza Kholnazarova Rustam qizi; Mukadas Murodova Ikromovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
This article explores the rise of the "Lost Generation" of American writers and their disillusionment following the devastation of World War I. It examines how this experience shaped their literary works, characterized by a loss of faith in traditional values and a sense of alienation. The article contrasts the Lost Generation with writers who emerged after World War II, who grappled with similar themes but also focused on social and political issues in America. James Jones' novel "From Here to Eternity" is highlighted as a powerful portrayal of the human cost of war.